Al-Idārah al-Islāmiyyah bi Indūnīsiyyā - Alirman Hamzah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
For some people, religion is often regarded as obstacles in the development of society. However, not all matters relating to the development, both in political, economic and social, hampered by religious factors. In fact, not a few religious factors play a very positive role in community development. In that regard, the founder of the Indonesian state, from the beginning has thought to do a kind of bureaucratization of religious issues, particularly Islam.There is a common assumption in modernization theory that religion represents an obstacle to modern social development. Despite this assumption, and despite the adherence of Indonesia'a New Order ideologues to modernization theory, the Indonesian goverment still recognizes the positive contibution to social development provided by religion.DOI: 10.15408/sdi.v5i1.762